First report on molecular epidemiology, seasonality and phylogeny of Toxoplasma gondii infecting goats from Khanewal district in Punjab, Pakistan - Aziz, Muhammad Naveed; Iqbal, Rana Khalid; Irfan, Muhammad; Parveen, Asia; Asif, Muhammad; Ozubek, Sezayi; Iqbal, Furhan (Elsevier, 2022)
Raising small ruminants is the main source of income for farmers in Pakistan. Economic losses caused by Toxoplasma gondii to small ruminants have been reported worldwide, however reports on molecular detection of T. gondii are lacking in Pakistan despite a large goat population. The current study was carried out from March 2019 till February 2020 to report the seasonal and molecular prevalence of T. gondii in different breeds of goats located in Khanewal district of Punjab, Pakistan. A total of 898 blood goat samples were collected during the four seasons and screened for T. gondii DNA by using PCR based on the amplification of ITS-1 partial sequence. Out of 898 goats, 48 (5.3%) were found positive to T. gondii. The prevalence of T. gondii varied according to season (Chi square test, P = 0.016) and the highest prevalence was observed in goats tested during the summer (8.8%) followed by the spring (5.7%), the winter (4.4%) and the autumn season (2.2%). PCR products positive to T. gondii were confirmed by DNA sequencing and BLAST analysis. Phylogenetic study based on ITS 1 gene provided evidence that the amplified isolates of T. gondii were highly conserved in Pakistani goats. Buck (Fischer exact test, P = 0.002) and farms containing other dairy animals next to goats (Fischer exact test, P = 0.001) and farms with a water supply from pools (Fischer exact test, P = 0.001) were more infected with T. gondii. Infected goats had a reduction on red blood cell count (Two-sample t test, P = 0.01) and hemoglobin concentration (Two-sample t test, P = 0.03) and an increase in the number of monocytes (%) (Two-sample t test, P = 0.05), mean cell hemoglobin (Two-sample t test, P = 0.01) and serum creatinine (Two-sample t test, P = 0.01) as compared to T. gondii uninfected goats. In conclusion, we report a relatively low PCR based prevalence of T. gondii in goats from Khanewal district as previously the serum ELISA test based prevalence of T. gondii in Pakistani goats varied between 19-52%. Control measures should be taken to eradicate T. gondii infection in goats of the study area.
Keywords: Toxoplasma gondii; goats; ITS-1 gene; Risk factors; Phylogenetic analysis; Pakistan